The right or wrong to the city? Understanding citizen participation in the pre- and post-COVID-19 eras in Malaysia - Seng Boon Lim; Muhammad Usman Mazhar; Jalaluddin Abdul Malek; Tan Yigitcanlar (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The right to the city concept is widely debated in academic discourse yet ambiguously executed in public discourse. In much of the discussion, the right to the city is advocated as a right that humans should claim - i.e., participating in urban space living. Nonetheless, constraints and limits are imposed on such advocacy, resulting in a tokenized implementation state. With such a background surmounting the COVID-19 pandemic era, this study is aimed at understanding the right to the city propagation and revealing the possible wrongs of such civic advocacy. Multiple cases in Malaysia were selected for analysis and as the discussion context representing the state-of-the-art aspect of right to the city in the context of an emerging country. Two potential misconceptions through the action of right to the city were identified: first, the concept of right to the city has the potential to infringe the centrality of power, which both citizens and the authority have to make clear; second, the lack of a sign of contribution from citizens poses a severe challenge to build a co-created urban space for all. This paper contributes to removing a blind spot - the possible wrong to the right to the city - and provides ideas to achieve authentic citizen participation.
Keywords: 650; COVID-19; citizen participation; co-created urban space; Malaysia; participatory governance; public policy; right to the city; social advocacy; urban policy; wrong to the city